Development of PISA-Type Mathematics Questions with Change and Relationship Content Based on the Jambi Context - Wika Septiani; Yelli Ramalisa; Feri Tiona Pasaribu; Agun Sutrianto (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
This study aims to describe the development process and determine the quality of PISA-type mathematics questions on the Change and Relationship content using the Jambi context for junior high school students in terms of validity, practicality, and effectiveness. This study uses the Research and Development (R&D) method by applying the ADDIE model proposed by Branc. The ADDIE model consists of five stages, namely analysis, design, development, implementation, dan evaluation. The research subjects were grade VIII II students of SMPs Pelita Raya Jambi. However, this research was carried out up to the development stage in accordance with the research objective, which was to produce an initial product in the form of validated PISA-type mathematics questions. The resulting product was 15 PISA-type mathematics questions that measured the ability to formulating, employing, and interpreting according to the PISA framework by integrating the cultural and environmental context of Jambi to make it more meaningful for students. PISA-type mathematical questions on the Change and Relationship content based on the Jambi context that were developed are declared valid, practical, and effective to be used as an alternative evaluation instrument foor mathematics learning at the junior high school level.